2013
DOI: 10.1002/zoo.21057
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Analysis of Tiger Night Housing Practices

Abstract: The systematic evaluation of changes in animal management practices is critical to ensuring the best possible welfare. Here, we examined the behavioral impacts of intermittently housing our six adult female tigers, who have been housed socially for much of their lives, individually overnight to allow for specialized care required by their advancing age. We looked for behavioral changes indicative of both positive and negative changes in welfare by monitoring time spent asleep, sleeping position, body position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This datum is shared by only two previous studies. Observers of a group of six female tigers recorded percentages of pacing of 0.47% of all scans when housed at night in a group and of 0.61% when housed at night alone (Miller et al, 2013), and the three tigers involved in the study by Lyons and colleagues (1997) did not pace at all. Conversely, the majority of studies in this field reported higher values: between 4.67 and 23.91% in 15 animals hosted in nine European zoos (De Rouck et al, 2005), 16.43% in a review by Clubb and Mason (2007), nearly 60% in two tigers observed before a feeding enrichment experiment (Bashaw et al, 2003), and an average of 23.02 ± 14.27% recorded in 19 captive tigers in Nandakanan Zoological Park (India) (Mohapatra et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…This datum is shared by only two previous studies. Observers of a group of six female tigers recorded percentages of pacing of 0.47% of all scans when housed at night in a group and of 0.61% when housed at night alone (Miller et al, 2013), and the three tigers involved in the study by Lyons and colleagues (1997) did not pace at all. Conversely, the majority of studies in this field reported higher values: between 4.67 and 23.91% in 15 animals hosted in nine European zoos (De Rouck et al, 2005), 16.43% in a review by Clubb and Mason (2007), nearly 60% in two tigers observed before a feeding enrichment experiment (Bashaw et al, 2003), and an average of 23.02 ± 14.27% recorded in 19 captive tigers in Nandakanan Zoological Park (India) (Mohapatra et al, 2014).…”
Section: Discussionmentioning
confidence: 94%